Sulfurization- Desulfurization of Iron-Calcium Oxygen Carriers during Chemical Looping Combustion of Syngas - Chen, Yu-Lun; Ku, Young; Chang, Ya-Chun (Aerosol and air quality research, 2024)
Chemical looping combustion of SO 2 -containing syngas with various fabricated iron-calcium oxygen carriers was studied to comprehend the sulfurization and desulfurization of oxygen carriers during combustion. Experimental results indicated calcium-iron oxygen carriers fabricated with CaO:Fe 2 O 3 weight ratio of 3:7 and calcined at 800°C (CaFe-378) was suitable for chemical looping combustion of syngas. CaFe 2 O 4 was noticed to be the dominant crystalline phase in CaFe-378 even after 10 redox operations. Reduction kinetics for chemical looping combustion of both H 2 or CO in syngas with CaFe-378 were adequately described by the 2-dimension diffusion model. The activation energies of H 2 and CO with CaFe-378 were determined to be 35.4 kJ mol −1 and 46.0 kJ mol −1 , respectively. Calcium sulfide (CaS) was generated during the chemical looping combustion of SO 2 -containing syngas with CaFe-378. CaS was further oxidized to CaSO 4 on the surface of CaFe-378 during air regeneration, which might inhibit the complete regeneration of iron oxides. Satisfactory regeneration of sulfurized oxygen carriers was accomplished by introducing hydrogen after the air-regeneration because of the reduction of calcium sulfate to calcium oxide.